The α-Glucosidase Inhibition Activities of Phaeochromycins D and E Isolated from Marine Streptomyces sp. FJ0218 - Pingfa Lin; Mianmian Shi; Feifei Wang; Yong Lin; Yongbiao Zheng (Molecules)
Marine Streptomyces are an important source of naturally occurring active compounds. Out of 23 marine Streptomyces strains, 1 strain of Streptomyces sp. FJ0218 was selected for its high activity in inhibiting α-glucosidase. Two polyketides, phaeochromycins D (2) and E (1), were isolated from the fermentation broth of this strain using bioactivity-guided column chromatography over RP-18, Sephadex LH-20, and silica gel. Their structures were determined using NMR data, HR-EI-MS, and single-crystal X-ray crystallography. Phaeochromycins D (2) and E (1) exhibited inhibitory activity against α-glucosidase, with IC50 values of 10 mM and 25 mM, respectively. Lineweaver–Burk plots revealed that phaeochromycin E (1) acts as an uncompetitive inhibitor, while phaeochromycin D (2) acts as a non-competitive inhibitor. These findings suggest that there is potential for the pharmacological regulation of glucose levels through the use of polyketide phaeochromycins, emphasizing their significant impact on glucose management.